Maternal mortality due to cardiac disease in low‐ and middle‐income countries - Heemelaar, S; Petrus, A; Knight, M; van den Akker, T (Wiley, 2020)
Objectives To assess the frequency of maternal death (MD) due to cardiac disease in low‐ and middle‐income countries (LMIC).